Long-term straw return influenced ammonium ion retention at the soil aggregate scale in an Anthrosol with rice-wheat rotations in China - Wen-zhao ZHANG; Xiao-qin CHEN; Huo-yan WANG; Wen-xue WEI; Jian-min ZHOU (Journal of Integrative Agriculture)
Soil aggregates are an important controlling factor for the physico-chemical and biological processes such as ammonium (NH4+) retention. Straw return to the field is increasingly recommended to promote soil carbon (C) sequestration and improve crop yields. However, the effects of straw return on NH4+ retention at soil aggregate level in agricultural soils have seldom been investigated. This study aimed to evaluate the influences of long-term straw return on NH4+ adsorption and fixation in microaggregates (<0.25 mm) with or without soil organic carbon (SOC) oxidization. Soil samples were collected from plots of three treatments, i.e., no fertilizer (CK), inorganic NPK fertilizers (NPK), and inorganic NPK fertilizers with rice straw return (NPKS), from a 20-year-old field trial with rice-wheat rotations in Taihu Lake Region, China. Soil aggregates were separated using wet-sieving method. The SOC of microaggregates was oxidized by H2O2. The results showed that long-term straw return significantly increased SOC and NH4+ adsorption, but inhibited NH4+ fixation in microaggregates. NH4+ adsorption potential and strength - obtained from adsorption isotherms - increased, but NH4+ fixation decreased along with increasing SOC in microaggregates, indicating the important role of SOC in NH4+ adsorption and fixation. This was verified by the SOC oxidization test that showed a relative decrease in NH4+ adsorption potential for the NPKS treatment and an increase in NH4+ fixation in all three treatments. Therefore, long-term straw return influences NH4+ adsorption and fixation by enhancing SOC content and could improve N availability for crop uptake and minimize applied N fertilizer losses in rice-wheat cropping systems.